Diseño de un módulo de selección preliminar de sistemas de levantamiento artificial para el manual general de completamiento de Ecopetrol S.A. (2017)
The current project refers to a module of preliminary selection of artificial lift systems for Ecopetrol S.A. which compiles in a Web App, a selection matrix and an occurrences map, both explained with a user manual. The general idea for the occurrences map is to recognize the distribution of artificial lift methods in the geographic zone which is to be reasoned about. With this map will be possible to know which artificial lift method dominates in that area, and to have an initial idea of what will be chosen for the artificial lift method.